Shopping With NutritionIn Mind - The Star, Joseph Loh (2008)
WITH rising food prices consumers are now looking for ways to get the most out of their ringgit Malaysians have the choice of buying either fresh or frozen produce and depending on the product frozen foods are sometimes priced lower than fresh foods.